Assessing distribution shifts and ecophysiological characteristics of the only Antarctic winged midge under climate change scenarios - Contador Mejias, Tamara Andrea; Ganan, Melisa; Bizama, Gustavo; Fuentes-Jaque, Guillermo; Morales, Luis; Rendoll, Javier; Simoes, Felipe; Kennedy, James; Rozzi Marin, Ricardo Roberto; Convey, Peter (My University, 2020)
Parts of Antarctica were amongst the most rapidly changing regions of the planet during the second half of the Twentieth Century. Even so, today, most of Antarctica remains in the grip of continental ice sheets, with only about 0.2% of its overall area being ice-free. The continent's terrestrial fauna consists only of invertebrates, with just two native species of insects, the chironomid midges Parochlus steinenii and Belgica antarctica. We integrate ecophysiological information with the development of new high-resolution climatic layers for Antarctica, to better understand how the distribution of P. steinenii may respond to change over the next century under different IPCC climate change scenarios. We conclude that the species has the potential to expand its distribution to include parts of the west and east coasts of the Antarctic Peninsula and even coastal ice-free areas in parts of continental Antarctica. We propose P. steinenii as an effective native sentinel and indicator species of climate change in the Antarctic.
Keywords: Peninsula; Antarctic ice sheet